2021
DOI: 10.21203/rs.3.rs-506335/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of Survival Outcomes with or Without Para-aortic Lymphadenectomy in Surgical Patients with Stage IB1-IIA2 Cervical Cancer in China from 2004-2016

Abstract: Background: Current opinions on whether surgical patients with cervical cancer should undergo para-aortic lymphadenectomy at the same time are inconsistent. The present study examined differences in survival outcomes with or without para-aortic lymphadenectomy in surgical patients with stage IB1-IIA2 cervical cancer.Methods: We retrospectively compared the survival outcomes of 8802 cervical cancer patients with stage IB1-IIA2 (FIGO 2009) from 37 hospitals in mainland China, who underwent abdominal radical hyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The overall grasp of the visual field avoids the omission of small active bleeding foci in the surgical field of view, and can effectively stop bleeding in time, thereby significantly reducing the amount of bleeding on the surgical wound and avoiding the occurrence of major bleeding. [46][47][48] The results of this study have showed that the time of the time to the first passage of flatus in the LRH is earlier than that of ARH. The possible reason for the difference may be that laparoscopic surgery avoids the touch of the abdominal retractor, gauze and operator's gloves on the intestine, and the less intestinal tract manipulations in the LRH reduce irritation to the patient's gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The overall grasp of the visual field avoids the omission of small active bleeding foci in the surgical field of view, and can effectively stop bleeding in time, thereby significantly reducing the amount of bleeding on the surgical wound and avoiding the occurrence of major bleeding. [46][47][48] The results of this study have showed that the time of the time to the first passage of flatus in the LRH is earlier than that of ARH. The possible reason for the difference may be that laparoscopic surgery avoids the touch of the abdominal retractor, gauze and operator's gloves on the intestine, and the less intestinal tract manipulations in the LRH reduce irritation to the patient's gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 61%
“…When the laparoscopic eyepiece is retreated, the surgical field of view can be expanded, and the operator’s awareness of the operation can be improved. The overall grasp of the visual field avoids the omission of small active bleeding foci in the surgical field of view, and can effectively stop bleeding in time, thereby significantly reducing the amount of bleeding on the surgical wound and avoiding the occurrence of major bleeding 46–48…”
Section: Discussionmentioning
confidence: 99%